The most common persistent symptoms in patients with COVID-19 who were evaluated in the Internal Medicine polyclinic - Koç, Zeynep; Akın, Seydahmet (The European Research Journal, 2023)
Objectives: To identify continuing symptoms of individuals in the post-COVID period. To begin with our study was planned to research the most common persistent symptoms in the post-COVID period, and additionally to research whether or not there were differences between the most frequent initial symptoms in the 1st, 2nd and 3rd waves of the pandemic. Methods: Cases attending the internal medicine clinic infected with COVID-19 who were minimum 120 days past the infection were included in the study. The study was shaped by responses of cases to open-ended questions. Results: From a total of 2,802 clinical attendances, 1,005 cases were included in the study. Of cases, 9.3% required clinical monitoring and 1.7% required intensive care during infection. The mean number of persistent symptoms was 1.38, with the most common persistent symptoms being 11.2% fatigue/tiredness, 6.1% shortness of breath, and 4.6% back and low back pain. Mean number of initial symptoms was 1.63, with the most common initial symptoms being 21.2% fatigue, 19.4% fever and 19.1% headache. Persistent chest pain was most common among those infected in the 1st wave, while there were no other significant differences observed between pandemic waves. Conclusions: The most common persistent symptoms were consistent with the general literature data; however, our condition of minimum 120 days past infection allowed a range of symptoms to ameliorate. Our results are more realistic in this way. A range of rare persistent symptoms emerging in our results were not encountered in the literature, while our study is unique as there is no other study comparing pandemic periods.